1993
DOI: 10.1111/j.1471-4159.1993.tb09843.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication: Regional Variability in DNA Fragmentation After Global Ischemia Evidenced by Combined Histological and Gel Electrophoresis Observations in the Rat Brain

Abstract: We have studied whether the delayed cell death induced by transient forebrain ischemia is associated with an internucleosomal cleavage of DNA into oligonucleosome-sized fragments. The integrity of genomic DNA in various brain regions after a 20-min four-vessel ischemia was examined using gel electrophoresis. We found typical ladders of oligonucleosomal DNA fragments in the striatum and in the Ammon's horn. In the latter we also often found a random DNA degradation as a smear pattern. These findings were reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(76 citation statements)
references
References 14 publications
4
69
1
2
Order By: Relevance
“…The domination of order even late after the initial ischemic period strengthens the suggestion, despite the absence of morphological evidence, that ischemic neurons are using some component of the apoptotic machinery. The accu mulating evidence in support of this conclusion from our own studies and those in other laborato ries (Heron et al, 1993;Linnik et al, 1993;Mac Manus et al, 1993;Okamoto et al, 1993;Tominaga et al, 1993;MacManus et al, 1994;Sei et al, 1994), now also including studies of epilepsy (Pollard et al, 1994), indicates that such research might lead to discoveries of new molecular targets for drug inter vention in the debilitating postischemic neuronal degeneration of stroke.…”
Section: N H S N H Sn Hs N H Ssupporting
confidence: 70%
“…The domination of order even late after the initial ischemic period strengthens the suggestion, despite the absence of morphological evidence, that ischemic neurons are using some component of the apoptotic machinery. The accu mulating evidence in support of this conclusion from our own studies and those in other laborato ries (Heron et al, 1993;Linnik et al, 1993;Mac Manus et al, 1993;Okamoto et al, 1993;Tominaga et al, 1993;MacManus et al, 1994;Sei et al, 1994), now also including studies of epilepsy (Pollard et al, 1994), indicates that such research might lead to discoveries of new molecular targets for drug inter vention in the debilitating postischemic neuronal degeneration of stroke.…”
Section: N H S N H Sn Hs N H Ssupporting
confidence: 70%
“…Linnik and colleagues (1993) first provided evidence for programmed cell death by showing that inhibition of protein synthesis was neuroprotective in a model of transient global ischemia. Subsequent studies identified DNA laddering and sensitive indicators of DNA damage associated with apoptosis (Heron et al, 1993;Petito et al, 1997). In addition, histopathological verification of injury models supports the hypothesis that at least a subpopulation of neurons die by apoptotic mechanisms.…”
Section: Cell Death Mechanismsmentioning
confidence: 72%
“…However, there is now compelling evidence in a number of neuronal cell types, including CGC, that apoptosis as well as necrosis underlie the death of neurones after an excitotoxin exposure (Kure et al, 1991;Heron et al, 1993;Linnik et al, 1993;MacManus et al, 1993MacManus et al, , 1994Ankarcrona et al, 1995; FIG. 8.…”
Section: Figmentioning
confidence: 99%